The development of pancreatic cancer is accompanied by significant changes in the immune response in genetically predisposed mice - Daniluk, Urszula; Świdnicka-Siergiejko, Agnieszka; Daniluk, Jarosław; Rusak, Małgorzata; Dąbrowska, Milena; Guzińska-Ustymowicz, Katarzyna; Pryczynicz, Anna; Dąbrowski, Andrzej (Frontiers in Oncology, 2025)
PurposeThe pathogenesis of pancreatic cancer (PC) is extremely complex and involves genetic and environmental factors, as well as significant changes in the immune response to tumor cells from the loss of immune surveillance to the development of immunotolerance to cancer. Currently available literature data on this subject is inconsistent. The purpose of our study was to evaluate the status of dendritic cells (DC) and other immune cells in the pancreas and blood of mice genetically predisposed to pancreatic cancer (KrasG12D mutation). The second objective was to assess the impact of fecal microbiota transplantation (FMT) from PC mice on pancreatic tumor development and alterations in pancreatic and blood immune cell counts in mice genetically predisposed to PC.MethodsWe used LSL-K-RasG12D mice, which possess the conditional knock-in mutant K-RasG12D driven by its endogenous promoter and Ela-CreERT mice, which express tamoxifen-regulated CreERT specifically in pancreatic acinar cells under the control of a full-length elastase gene promoter. The immunophenotype of immune cells separated from pancreatic tissue and circulating blood was analyzed with the use of multicolor flow cytometry and immunochemistry staining. Fecal pellets from LSL-K-RasG12D mice, that developed PC after the cerulein (CER) treatment, were collected and transplanted into animals previously treated with the antibiotic.ResultsUsing immunohistochemistry and flow cytometry, we found that in mice genetically predisposed to PC, cerulein (CER) administered intraperitoneally induced tumor growth and inflammatory cell infiltration in pancreatic tissue, but without affecting immune cell differentiation in the blood. In contrast, orally administered FMT activated the immune system in the gastrointestinal tract, leading to generalized immune cell activation, as observed in the blood, and local infiltration of cells in the pancreatic tissue of Kras mutant mice that developed pancreatic tumors. Interestingly, immunohistochemical evaluation of pancreatic tissue revealed that the Kras mutation alone causes increased infiltration of CD11b+, CD20+, CD3+, CD4+, and CD8+ cells. After FMT, there was a trend toward an increased intensity of infiltration by these immune cells, with the exception of CD11b+.ConclusionsOur data suggest that pancreatic cancer development in genetically predisposed mice is accompanied by profound changes in immune cell composition. Treatment with tumor-inducing agents such as CER or FMT from tumor-bearing mice, accelerated PC progression. The type of immune system response, systemic or local, in mice with pancreatic cancer depends on the route of entry of the inflammatory agent. Oral administration of FMT activated the systemic immune response, in contrast to the intraperitoneal injection of CER.